CREAREA OMULUI – LUCRAREA COMUNĂ, IUBITOARE ȘI LIBERĂ A PREASFINTEI TREIMI. TEMEIUL RESPECTĂRII DREPTURILOR OMULUI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The creation of man, the common, loving and free work of the Most Holy Trinity. The basis of respect for human rightsOur Saviour Jesus Christ comes into the world sent precisely to reveal from the beginning the creative and saving life and love of the Holy Trinity. He says: „I record what I have seen in my Father” ( John 8,38), also his prayer is the witness of communion with the Father: „Jesus said to him: Did I not tell you that if you believe you will see the glory of God?”. So they lifted up the stone, and Jesus lifted up his eyes and said: „Father, I thank you for having listened to me; I knew that you always listen to me, but for the sake of the crowd standing around, I said that they should believe that you sent me” ( John 11,40-42); „And now you, Father, glorify me with the glory that I had with you before the world was” ( John 17, 5). God`s creation of Man and endowing human nature with His divine image is the strongest argument for both respect for human freedom and dignity. God is the source and foundation of love and freedom through the act of creation. Therefore, freedom and love are both God`s gifts to man and virtues, powers received by man in the act of creation through which he puts himself in harmony with the prototype and with other people (1 John 4,19-21). One of the outstanding characteristics of this bond of man with God is primarily freedom, as an expression of the sovereighnty of the image. Just as God is free in his acts, so man is guided by his own free will towards what is right for his nature. In this freedom lies the joy of the reward of human toil as a reward for virtue. Man is free when he lives in a virtuous way and becomes like God. Our Saviour Jesus Christ Himself says: „I am the Way, the Truth and the Life. No one comes to the Father except through me” ( John 14,6) and „you will know the truth , and the truth will set you free” ( John 8,32), for, „a new commandment I give to you, that you love one another as I have loved you. By this all will know that you are my disciples, if you have love for one another” ( John 13,34-35). St. Paul says: „The Lord is the Spirit, and where the Spirit of the Lord is, there is liberty” (II Corinthians 3,17), abd in another place: „For as many as are moved by the Spirit of God are sons of God. For you have not again received a spirit of bondage to fear, but you have received the Spirit of adoption, through whom we cry Abba! Father, the Spirit Himself testifies with our spirit that we are sons of God” (Romans 8,14-16).